Combined moist airtight storage and feed fermentation of barley by the yeast Wickerhamomyces anomalus and a lactic acid bacteria consortium - Borling Welin, Jenny; Lyberg, Karin; Passoth, Volkmar; Olstorpe, Matilda (Frontiers in Plant Science, 2015)
This study combined moist airtight storage of moist grain with pig feed fermentation. Starter cultures with the potential to facilitate both technologies were added to airtight stored moist crimped cereal grain, and the impact on storage microflora and the quality of feed fermentations generated from the grain was investigated. Four treatments were compared: three based on moist barley, either un inoculated (M), inoculated with Wickerhamomyces anomalus (W), or inoculated with W. anomalus and LAB starter culture, containing Pediococcus acidilactici DSM 16243, Pediococcus pentosaceus DSM 12834 and Lactobacillus plantarum DSM 12837 (WLAB); and one treatment based on dried barley (D). After 6 weeks of storage, four feed fermentations FM, FW, FWLAB, and FD, were initiated from M, W, WLAB and D, respectively, by mixing the grain with water to a dry matter content of 30%. Each treatment was fermented in batch initially for 7 days and then kept in a continuous mode by adding new feed daily with 50% back-slop. During the 6 week storage period, the average water activity decreased in M, W and WLAB from 0.96 to 0.85, and cereal pH decreased from approximately 6.0 at harvest to 4.5. Feed fermentation conferred a further pH decrease to 3.8 – 4.1. In M, W and WLAB, moulds and Enterobacteriaceae were mostly below detection limit, whereas both organism groups were detected in D. In fermented feed, Enterobacteriaceae were below detection limit in almost all conditions. Moulds were detected in FD, for most of the fermentation time in FM and at some sampling points in FW and FWLAB. Starter organisms, especially W. anomalus and L. plantarum comprised a considerable proportion of the yeast and LAB populations, respectively, in both stored grain and fermented feed. However, autochthonous Pichia kudriavzevii and Kazachstania exigua partially dominated the yeast populations in stored grain and fermented feed, respectively.